A regulatory perspective on local mobile communication network business in Europe: legitimacy considerations - Oxana Gisca; Marja Matinmikko-Blue; Petri Ahokangas; Jillian Gordon; Seppo Yrjölä (International Telecommunications Society (ITS), 2023)
Local cellular mobile communication networks have evolved as a novel concept and deployment model, and a prerequisite for their future emergence is the radio spectrum, which is a scarce resource. Regulatory approaches are expanding at the national, regional, and international levels making legitimacy of the local 5G and future 6G mobile communication networks an existing multi-faceted consideration. This paper provides an analysis of the regulatory approaches taken by national regulatory authorities (NRA) considering local 5G mobile communication networks. The focus is the European level, with Finland and UK as case examples. The article applies business model thinking to the regulatory realm of local mobile communication networks in Europe as an approach to the legitimacy considerations identified. The paper paves way to a new perspective for understanding and developing regulatory approaches and advancing sound and efficient regulatory actions.
Keywords: 330